2012
DOI: 10.1186/1475-2891-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Association of total energy intake and macronutrient consumption with colorectal cancer risk: results from a large population-based case-control study in Newfoundland and Labrador and Ontario, Canada

Abstract: Background Diet is regarded as one of the most important environmental factors associated with colorectal cancer (CRC) risk. A recent report comprehensively concluded that total energy intake does not have a simple relationship with CRC risk, and that the data were inconsistent for carbohydrate, cholesterol and protein. The objective of this study was to identify the associations of CRC risk with dietary intakes of total energy, protein, fat, carbohydrate, fiber, and alcohol using data from a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 54 publications
1
42
1
Order By: Relevance
“…One prospective cohort study reported a non-significant increase in the risk of death among U.S. adults who took iron at a dosage above the RDA (18 mg/day for premenopausal women) compared with non-users (41). Population-based case-control studies have shown 34% to 56% higher odds of iron supplement use among colorectal cancer cases than control subjects (42, 43). Recent systematic review and meta-analysis of epidemiologic studies have concluded that higher heme iron intake was associated with a trend towards higher risk of cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…One prospective cohort study reported a non-significant increase in the risk of death among U.S. adults who took iron at a dosage above the RDA (18 mg/day for premenopausal women) compared with non-users (41). Population-based case-control studies have shown 34% to 56% higher odds of iron supplement use among colorectal cancer cases than control subjects (42, 43). Recent systematic review and meta-analysis of epidemiologic studies have concluded that higher heme iron intake was associated with a trend towards higher risk of cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…Also, published epidemiologic findings has indicated that higher energy intake was associated with increased risk of specific type of cancer, e.g. prostate (Hsieh et al, 2003), breast (Sue et al, 2009), and colorectal cancer (Sun et al, 2012). However, the association between energy and endometrial cancer were ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient and total energy intakes were calculated by multiplying the frequency of consumption of each food by the nutrient content of the portion size based on the composition values from the 2005 Canadian Nutrient file. 12 Taking a similar grouping scheme to that used elsewhere, 3 we collapsed individual food items on the FFQ into 39 predefined food groups based on the roles of food in diet and cancer aetiology. Distinct food items were reserved as individual categories if it was deemed inappropriate to combine them (eg, jam, pies, beer and wine).…”
Section: Subjects and Methods Study Participantsmentioning
confidence: 99%
“…1 Geographically isolated in the Atlantic Ocean, NL has long maintained its traditional foods, a Western-style diet consisting of a large proportion of processed meat, red meat and insufficient vegetables. 11 Several studies have partially attributed the high CRC incidence rate in NL to its unique diet, [11][12][13] but no study has explored the association between the NL diet and its impact on survival among CRC patients.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%